The Influence of USDT Dominance on Volatility and Stock Market Performance in Indonesia - Putera, Muhammad Tommy Fimi; Ramadhani, Muhammad Harits Zidni Khatib (The Es Accounting And Finance, 2024)
This study aims to analyze the influence of USDT (Tether) dominance on the volatility and performance of the stock market in Indonesia. USDT, as one of the largest stablecoins in the world, plays a significant role in the global crypto market and can impact various asset classes including stocks. This study uses time series data covering the period from 2018 to 2023, focusing on the Indonesian stock market index (IHSG) and USDT dominance in the crypto market. The methods used in this research include multiple regression analysis to examine the relationship between USDT dominance and IHSG movements, as well as Granger Causality tests to evaluate whether USDT dominance can predict changes in stock market volatility. The results show a significant relationship between increased USDT dominance and increased stock market volatility in Indonesia. Additionally, USDT dominance is found to have a predictive effect on the decline in stock market performance, especially in unstable market situations. These findings have important implications for investors and policymakers in Indonesia, given the increasing interconnection between the crypto market and traditional financial markets. This study recommends tighter monitoring of stablecoin movements like USDT and enhanced financial literacy among market participants to anticipate potential volatility impacts.